Sphingolipids in Apoptosis - Tirodkar, T.S.; Voelkel-Johnson, C. (Experimental Oncology, 2012)
Forty years ago, the term “apoptosis” was introduced to describe a form of programmed cell death. Key players that mediate apoptosis at the molecular level such as caspases, death receptors, Bcl-2 family members have since been identified and their regulation remains a research focus of many laboratories. In 1993, approximately 20 years after the introduction of apoptosis, the sphingolipid ceramide was first linked to this form of cell death. Sphingolipids are bioactive components of cellular membranes that are involved in numerous physiological functions. In this paper, we discuss the inherent complexities of sphingolipid signaling and elaborate on how sphingolipids, primarily ceramide, influence apoptotic events such as death receptor aggregation in the plasma membrane and pore formation at the mitochondria. Possible roles of sphingolipids in other subcellular compartments, such as the nucleus, endoplasmic reticulum and lysosomes are also discussed. We conclude by summarizing the recent developments in sphingolipid based cancer therapy. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.